Fast discovery of long patterns for association rules - Mustapha, N.; Sulaiman, M.N.; Othman, M.; Selamat, M.H. (Informa UK Limited, 2003)
The most time consuming process in discovering association rules is identifying the frequent patterns especially in the cases when the database contains long patterns. An algorithm called Flex for identifying frequent patterns especially efficient when the patterns are long is proposed by successive construction of the nodes lexicographic tree. The vertical counting strategy to facilitate fast discovery is used in support computation. The experimental result shows that Flex outperform Apriori, a well-known and widely used algorithm for patterns discovery.